TECHNOLOGY-ENHANCED PEDAGOGY FOR TEACHING ENGLISH AS AN APPLIED LANGUAGE IN HIGHER EDUCATION: A PRISMA REVIEW - Simron Krisnuarjati Hindom; Galuh Wuryaningtyas; Natalina Antonia dos Santos; Edeltrudis Patrisia Soge; Markus Budiraharjo (SOSIOEDUKASI, 2026)
Digital technology has increasingly shaped the teaching of English as an applied language in higher education. Although many university students are familiar with digital tools, educators often face challenges in selecting technologies that support meaningful learning outcomes. This study aimed to identify effective digital tools and summarize practical pedagogical implications for university-level English instruction. A systematic literature review (SLR) was conducted following PRISMA 2020 guidelines. Fifty journal articles were retrieved from Scopus, Web of Science, and Google Scholar. After screening and eligibility assessment, 16 studies were included for synthesis, representing experimental, quasi-experimental, mixed-methods, qualitative, survey-based, and conceptual analytical research. The findings show that Mobile-Assisted Language Learning (MALL), particularly vocabulary apps and digital flashcards, provides the most consistent evidence of effectiveness, especially for vocabulary acquisition and retention. AI-supported tools and intelligent personal assistants demonstrate skill-specific benefits, particularly for speaking practice, pronunciation awareness, learner autonomy, and engagement, while effects on receptive skills are less consistent. Emerging technologies such as chatbots, robotics, and virtual reality show promising potential but remain underrepresented in rigorous classroom-based research. Overall, the review highlights that technology is most effective when integrated with clear learning objectives, structured tasks, and teacher guidance. Practical recommendations are provided to support educators in selecting and implementing digital tools that align with instructional goals and learner needs